Significance of metastatic topography for the immunotherapy of cutaneous and ocular melanomas - Săftescu, Sorin (Rom J Ophthalmol, 2020)
PD-1 is expressed on the surface of activated T lymphocytes and belongs to the category of negative immune stimuli. Its blocking stimulates the immune response to tumor antigens. Ocular melanomas represent 3-4% of the total melanomas and have metastatic potential, especially to the liver but also to the lungs, skin, and bones. In the case of metastatic melanoma, immunotherapy has a unique role due to the lower frequencies of BRAF mutation in choroidal melanomas and consecutive exclusion from treatment with specific BRAF tyrosine kinase inhibitors. A retrospective observational study was performed in 42 patients who received immunotherapy (IT) with nivolumab for cutaneous and ocular metastatic melanomas, aimed at highlighting the association between the topography of metastases and the duration of immunotherapy until progressive disease. The results indicated the presence of liver metastases as a negative predictive factor for IT duration in patients with melanoma and the presence of lymphatic metastases as a predictive factor for longer IT in patients with melanoma under 65 years old.